2004
DOI: 10.1128/jb.186.19.6465-6476.2004
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal Pilin Subunit from the Insect Pathogen Xenorhabdus nematophila

Abstract: Xenorhabdus nematophila is an insect pathogen and produces protein toxins which kill the larval host. Previously, we characterized an orally toxic, large, outer membrane-associated protein complex from the culture medium of X. nematophila. Here, we describe the cloning, expression, and characterization of a 17-kDa pilin subunit of X. nematophila isolated from that protein complex. The gene was amplified by PCR, cloned, and expressed in Escherichia coli. The recombinant protein was refolded in vitro in the abse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
21
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 42 publications
3
21
0
Order By: Relevance
“…These vesicles appear in transmission electron microscopy as surface blebs and detached extracellular vesicles and have been shown to have a hemagglutinin function (185) and to contain sialidase activity that may be correlated to virulence (78). Similar outer membrane vesicles have been observed in Porphyromonas gingivalis, Pseudomonas fragi, and Xenorhabdus nematophilus, where it has been suggested that they may serve as a vehicle for toxins and attachment to host cells (80,109,132). Furthermore, similar vesicles in Pseudomonas aeruginosa have been shown to carry quinolone signaling molecules for intercellular signaling (153).…”
Section: Cell Surface Structuresmentioning
confidence: 62%
“…These vesicles appear in transmission electron microscopy as surface blebs and detached extracellular vesicles and have been shown to have a hemagglutinin function (185) and to contain sialidase activity that may be correlated to virulence (78). Similar outer membrane vesicles have been observed in Porphyromonas gingivalis, Pseudomonas fragi, and Xenorhabdus nematophilus, where it has been suggested that they may serve as a vehicle for toxins and attachment to host cells (80,109,132). Furthermore, similar vesicles in Pseudomonas aeruginosa have been shown to carry quinolone signaling molecules for intercellular signaling (153).…”
Section: Cell Surface Structuresmentioning
confidence: 62%
“…The proteins were applied on the surface of artificial diet and allowed to percolate down. One neonatal larva (24 h old) of H. armigera was released on the surface of the diet in each well (19), and the plates were incubated at 25°C (16-h-day-length periods) with 80% relative humidity. Mortality and larval weight were recorded periodically over the entire larval period.…”
Section: Methodsmentioning
confidence: 99%
“…MrxA was shown to be associated with outer membrane vesicles (OMVs) that exhibited oral toxicity toward the lepidopteran Helicoverpa armigera (25). Purified MrxA exhibited cytotoxic properties and recombinant MrxA displayed oral toxicity and functioned as a pore-forming toxin on targeted insect hemocytes (5,26).…”
mentioning
confidence: 99%